Trace Metals and 210Po Activity Concentrations in Macroalgae (Cystoseira Crinita and Halopteris Scoparia) and Seagrass (Cymodocea Nodosa) in Izmir Bay, Aegean Turkish Coast - Akakçe, Nurdan; Görgün, Aysun Uğur; Kizilkaya, Inci Tüney; Atay, Nevra Öztürk (Journal of Environmental Science and Engineering Technology, 2020)
Two types of macroalgae (Cystoseira crinita and Halopteris scoparia) and seagrass (Cymodocea nodosa) have been evaluated for their bioavailability as biomonitors of trace metals and 210Po in Izmir Bay during the period of October 2017-July 2018. The levels of Al, Fe, Zn, Mn and Pb in the samples were determined using energy dispersive x-ray fluorescence spectrometry. The activity concentrations of 210Po were measured by alpha spectrometry and the results have shown that C. nodosa were found to accumulate the maximum 210Po concentration in the winter. Besides, macroalgae (C.crinita and H. scoparia) were also found to accumulate 210Po at different levels in the same area. Additionaly, the investigated trace metals were determined in H. scoparia and C. nodosa in the winter. A seasonal fluctuations in trace metals and 210Po concentrations were observed in the study.